Factors of Depression and its Prevalence among Pregnant Females Attending Antenatal Clinics in Pakistan - Rizwan Farooq, Saima Afsar, Muntazir Mehdi, Muhammad Ali Jaffar, Sara Ashfaq, Usman Amin Hotiana (Pakistan Journal of Medical & Health Sciences, 2022)
Depression is a disorder that affects the persons mood and its incidence is one in four females occurs at any time in their lives, so it’s no wonder that pregnant women are also affected by this condition. However, depression during pregnancy is often misdiagnosed as fluctuations in a woman’s hormone levels are believed to be the cause of many of these changes. In the hope that a diagnosis can, be made at a very early stage and that preventive measures can be taken later, the first step is to govern the pervasiveness of depression in pregnant females. The available evidence of depression in pregnancy varies widely. We need relatively short estimates to determine the severity of a depressive illness and develop a coping strategy for disorders of depression. Aim: To access the depression prevalence among pregnant females admitted to the gynecology department. Place and Duration: In the Psychiatry department of Behavioral Sciences PGMI/AMC/LGH, Lahore and Timergara Psychiatry Clinic in Pakistan for the duration of six months from September 2021 to February 2022. Methods: Data were gathered from 250 pregnant women by randomly collecting samples during their antenatal visits. The Depression Standard Scale named the "Hamilton Rating Scale for Depression," was used and depression was labelled if score greater than 7 on the Standard Rating Scale. The analysis of the result was performed using the SPSS program and chi-square test. Results: The incidence of depression in gravid females was 82%. The study found 45 (18%) completely normal, 100 (40%) mild depression, 65 (26%) moderate depression, 28 (11.2%) had severe depression, and 12 (4.3%) were very severe depression. 0.013 was a statistically significant value of P. Conclusion: The data showed increased prevalence of depression among pregnant females in Pakistan, reaching 82%. Depression is much common in younger females, those with fewer births and pregnancies, and those living in a shared family system. Keywords: Depression; Prevalence; Pregnancy and Prenatal period; Psychiatric disorders and Mood disorders.